A missense mutation in the catalytic domain of O-GlcNAc transferase links perturbations in protein O-GlcNAcylation to X-linked intellectual disability. - Pravata, Veronica M; Gundogdu, Mehmet; Bartual, Sergio G; Ferenbach, Andrew T; Stavridis, Marios; Õunap, Katrin; Pajusalu, Sander; Žordania, Riina; Wojcik, Monica H; van Aalten, Daan M F (FEBS Lett, 2020)
X-linked intellectual disabilities (XLID) are common developmental disorders. The enzyme O-GlcNAc transferase encoded by OGT, a recently discovered XLID gene, attaches O-GlcNAc to nuclear and cytoplasmic proteins. As few missense mutations have been described, it is unclear what the aetiology of the patient phenotypes is. Here, we report the discovery of a missense mutation in the catalytic domain of OGT in an XLID patient. X-ray crystallography reveals that this variant leads to structural rearrangements in the catalytic domain. The mutation reduces in vitro OGT activity on substrate peptides/protein. Mouse embryonic stem cells carrying the mutation reveal reduced O-GlcNAcase (OGA) and global O-GlcNAc levels. These data suggest a direct link between changes in the O-GlcNAcome and intellectual disability observed in patients carrying OGT mutations.
Keywords: Animals; Catalytic Domain; Cell Line; Glycosylation; Humans; Intellectual Disability; Mice; Models, Molecular; Mutation, Missense; N-Acetylglucosaminyltransferases